Involving citizens' occupation-based knowledge in public health planning: Why and how. Issue 1 (2nd January 2018) - Horghagen, Sissel; Magnus, Eva; Anthun, Kirsti Sarheim; Knudtsen, Margunn Skjei; Wist, Guri; Lillefjell, Monica
ABSTRACT: Health promotion has generally relied on traditional forms of community planning without including citizens, despite their occupation-based experiences and knowledge about the society in which they live. Acknowledging that it is a challenge for stakeholders to involve citizens in public health planning, this study explores why and how stakeholders might facilitate the involvement of citizens in public health planning as a part of a municipality's health promotion work. Data were obtained through interviews with six key stakeholders (f=4, m=2) working in the local community. Qualitative analysis generated two themes and six subthemes: I) Involving whom and why, with four subthemes of i) Addressing justice, ii) Generating ownership, iii) Developing trust and a feeling of togetherness, and iv) Concretizing the history, values, uniqueness, and identity of the city; as well as II) Considering differences, with two subthemes of i) Accommodating creativity and ii) Building confidence. The discussion highlights how occupation-based knowledge from citizens can strengthen the quality of public health planning and the successful local implementation of health promotion policy.